Secular changes in the age-specific prevalence of diabetes among U.S. adults: 1988-2010 - Cheng, Yiling J; Imperatore, Giuseppina; Geiss, Linda S; Wang, Jing; Saydah, Sharon H; Cowie, Catherine C; Gregg, Edward W (Diabetes care, 2013)
To examine the age-specific changes of prevalence of diabetes among U.S. adults during the past 2 decades. This study included 22,586 adults sampled in three periods of the National Health and Nutrition Examination Survey (1988-1994, 1999-2004, and 2005-2010). Diabetes was defined as having self-reported diagnosed diabetes or having a fasting plasma glucose level ≥ 126 mg/dL or HbA1c ≥ 6.5% (48 mmol/mol). The number of adults with diabetes increased by 75% from 1988-1994 to 2005-2010. After adjusting for sex, race/ethnicity, and education level, the prevalence of diabetes increased over the two decades across all age-groups. Younger adults (20-34 years of age) had the lowest absolute increase in diabetes prevalence of 1.0%, followed by middle-aged adults (35-64) at 2.7% and older adults (≥ 65) at 10.0% (all P < 0.001). Comparing 2005-2010 with 1988-1994, the adjusted prevalence ratios (PRs) by age-group were 2.3, 1.3, and 1.5 for younger, middle-aged, and older adults, respectively (all P < 0.05). After additional adjustment for body mass index (BMI), waist-to-height ratio (WHtR), or waist circumference (WC), the adjusted PR remained statistically significant only for adults ≥ 65 years of age. During the past two decades, the prevalence of diabetes increased across all age-groups, but adults ≥ 65 years of age experienced the largest increase in absolute change. Obesity, as measured by BMI, WHtR, or WC, was strongly associated with the increase in diabetes prevalence, especially in adults <65.